2023
DOI: 10.1111/apt.17428
|View full text |Cite
|
Sign up to set email alerts
|

Trends in risk factor control and treatment among patients with non‐alcoholic fatty liver disease and type 2 diabetes between 2000 and 2020: A territory‐wide study

Abstract: Background & Aims: We aimed to determine the trends in risk factor control and treatment among patients with non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes (T2D) in 2000-2020. Methods: We conducted a territory-wide cohort study of adult patients with NAFLD and T2D diagnosed between 1 January 2000 and 31 July 2021 in Hong Kong. T2D was defined by use of any anti-diabetic agents, laboratory tests and/or diagnosis codes. Results: This study included 16,084 patients with NAFLD and T2D (mean age, 54.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
(130 reference statements)
1
4
0
Order By: Relevance
“…Multivariate Logistic regression analysis found that smoking history and drinking history were independent risk factors for persistent hypertension (OR>1 and P <0.05) in diabetic patients with hypertension, the risk of persistent hypertension increased with age, BMI, FBG, HbA1c and LDL-C (OR>1 and P <0.05), and taking antihypertensive drugs, hypoglycemic drugs and lipid-lowering drugs were independent protective factors for persistent (OR <1 and P <0.05) in diabetic patients with hypertension. The results of this study confirmed that smoking, drinking, increased age, increased BMI, hyperglycemia and high levels of LDL-C are independent risk factors for hypertension, which has a good reference for blood pressure control in diabetic patients with hypertension ( 16 ). In addition, it was found in this study that taking conventional antihypertensive drugs, hypoglycemic drugs and lipid-lowering drugs were protective factors for persistent hypertension in patients, without correlation between the addition of liraglutide (GLP-1RAs) and persistent hypertension in the research subjects.…”
Section: Discussionsupporting
confidence: 72%
“…Multivariate Logistic regression analysis found that smoking history and drinking history were independent risk factors for persistent hypertension (OR>1 and P <0.05) in diabetic patients with hypertension, the risk of persistent hypertension increased with age, BMI, FBG, HbA1c and LDL-C (OR>1 and P <0.05), and taking antihypertensive drugs, hypoglycemic drugs and lipid-lowering drugs were independent protective factors for persistent (OR <1 and P <0.05) in diabetic patients with hypertension. The results of this study confirmed that smoking, drinking, increased age, increased BMI, hyperglycemia and high levels of LDL-C are independent risk factors for hypertension, which has a good reference for blood pressure control in diabetic patients with hypertension ( 16 ). In addition, it was found in this study that taking conventional antihypertensive drugs, hypoglycemic drugs and lipid-lowering drugs were protective factors for persistent hypertension in patients, without correlation between the addition of liraglutide (GLP-1RAs) and persistent hypertension in the research subjects.…”
Section: Discussionsupporting
confidence: 72%
“…The recent study performed by Zhang et al provides interesting data regarding the trends in risk factor control and treatment among a large territory‐based cohort of adult patients with NAFLD and T2DM in Hong Kong between 2000 and 2020 8 . Among 16,084 patients included in this study, the percentage of patients achieving individualised haemoglobin A1c (HBA1c) target increased from 44.5% to 64% from 2000–2005 to 2016–2020.…”
mentioning
confidence: 77%
“…Declaration of personal interests : The authors' declarations of personal and financial interests are unchanged from those in the original article 1 …”
Section: Acknowledgementsmentioning
confidence: 99%
“…This article is linked to Zhang et al papers. To view these articles, visit https://doi.org/10.1111/apt.17428 and https://doi.org/10.1111/ apt.17467 Xinrong Zhang 1,2 Grace Lai-Hung Wong 1,2 Vincent Wai-Sun Wong 1,2 Terry Cheuk-Fung Yip…”
Section: Fu N D I N G I N Fo R M Ati O Nmentioning
confidence: 99%
See 1 more Smart Citation